A new era of systems neuroscience in aphasia?. Issue 7 (3rd July 2018) - Ulm, Lena; Copland, David; Meinzer, Marcus
ABSTRACT: Background: Systems neuroscience acknowledges that human brain function relies on complex interactions between specialised brain regions that are organised in widely distributed functional brain networks. This approach provides a powerful framework to investigate how local structural damage such as a stroke impacts language network reorganisation in aphasia patients and its relation to recovery. Aims: In this paper we aim to familiarise the readers with the concept of systems neuroscience and its application in aphasia imaging. Main Contribution: We briefly describe common analytic methods used in systems neuroscience with a focus on magnetic resonance imaging (MRI) based connectivity analyses. We describe task-based and resting-state functional MRI and diffusion weighted imaging based approaches that allow assessing functional and structural network characteristics in the human brain. Subsequently, we discuss recent studies that have used different network-level approaches to investigate recovery and treatment-induced neural reorganisation in aphasia. Conclusions: This illustrative review highlights the potential of the novel systems neuroscience approach to improve our understanding of the neural mechanisms underlying recovery and treatment response in aphasia. We also discuss a number of key issues that need to be addressed in this emerging field before it can effectively contribute to clinical decision-making.